A Critical Perspective on the Role of Psychotropic Medications in Mental Health Courts. (February 2013) - Hughes, Shannon; Peak, Terry
Mental health courts represent an opportunity for individuals diagnosed with a mental illness and involved in the criminal justice system to participate in community-based treatment in lieu of incarceration. Individuals who agree to participate also agree to court-ordered mental health treatment that often includes a requirement to take prescribed psychotropic medications. Despite controversies concerning medications' efficacy and growing evidence of long-term harms, a critical discussion of medications' role in mental health courts remains absent in the literature. We review current research findings related to psychotropic medications and pose legal and ethical questions of their mandated status in mental health courts. We offer recommendations for mental health courts to adopt evidence-based policies that prioritize participant self-determination in regard to medication-taking and discuss challenges to implementing our recommendations.